Unexpected Aldehyde-Catalyzed Reaction of Imidazole N-Oxides with Ethyl Cyanoacetate - Kutasevich, Anton V.; Efimova, Anna S.; Sizonenko, Marina N.; Perevalov, Valery P.; Kuz’mina, Ludmila G.; Mityanov, Vitaly S. (Synlett, 2020)
The reaction of 2-unsubstituted imidazole N-oxides with ethyl cyanoacetate and aromatic aldehydes leads to the formation of ethyl 2-cyano-2-(1,3-dihydro-2H-imidazole-2-ylidene)acetates. The reaction proceeds through an initial [3+2] cycloaddition, followed by cleavage of the cycloadduct and regeneration of the aldehyde, which essentially plays a catalytic role.
Keywords: imidazole oxides; 1,3-dipolar cycloaddition; reaction mechanism; organocatalysis; multicomponent reaction; [3+2] cycloaddition